Biomaterial-based microstructures fabricated by two-photon polymerization microfabrication technology. Issue 59 (25th October 2019) - Wang, Xiaoying; Wei, Zhenping; Baysah, Charles Zuwu; Zheng, Meiling; Xing, Jinfeng
Abstract : Two-photon polymerization (TPP) microfabrication technology can freely prepare micro/nano structures with different morphologies and high accuracy for micro/nanophotonics, micro-electromechanical systems, microfluidics, tissue engineering and drug delivery. Abstract : Two-photon polymerization (TPP) microfabrication technology can freely prepare micro/nano structures with different morphologies and high accuracy for micro/nanophotonics, micro-electromechanical systems, microfluidics, tissue engineering and drug delivery. With the broad application of 3D microstructures in the biomedical field, people have paid more attention to the physicochemical properties of the corresponding materials such as biocompatibility, biodegradability, stimuli responsiveness and immunogenicity. Therefore, microstructures composed of biocompatible synthetic polymers, polysaccharides, proteins and their complexes have been widely studied. In this review, we briefly summarize the TPP mechanism, the photoinitiators for TPP microfabrication, photoresist based on biomaterials, their corresponding microstructures and subsequently their biomedical applications. We will point out the issues in previous research and provide a useful perspective on the future development of TPP microfabrication technology.